Civic education as the key to building peaceful schools in Indonesian - Istianah, Anif; Darmawan , Cecep; Sundawa, Dadang; Fitriasari, Susan; Irawan, Hendri (Universitas Ahmad Dahlan, 2025)
Indonesia’s cultural diversity, encompassing various ethnicities, religions, and languages, presents both opportunities and challenges for social cohesion. Schools play a vital role in fostering national unity, with Civic Education (Pancasila and Civic Education or PPKn) serving as a key tool in promoting inclusivity and peace. This study examines the role of PPKn in building peaceful schools within Indonesia’s diverse primary education context, identifying its contributions, challenges, and areas for improvement. This study analyzes peer-reviewed articles, policy documents, and educational reports published in the last decade using a qualitative literature review. Content analysis was conducted to identify key themes related to Civic Education, character formation, and diversity management in schools. Findings indicate that integrating Pancasila values such as tolerance, social justice, and cooperation into PPKn fosters students’ critical thinking, empathy, and appreciation for diversity. However, challenges persist, including limited teacher preparedness, outdated teaching approaches, and curriculum gaps in addressing contemporary issues like digital-era conflicts and social polarization. Strengthening teacher training, implementing participatory learning methods, and adopting inclusive pedagogies are essential for effective PPKn delivery. This study concludes that a value-based and adaptive Civic Education approach is crucial for promoting peace in Indonesian schools. It recommends curriculum updates, enhanced teacher development, and stronger school-community collaboration to reinforce social harmony.